Metarrepresentação em tradução: uma análise relevantista dos processos inferenciais de tradutores expertos na tradução de textos sensíveis (sagrados) - Geraldo Luiz de Carvalho Neto (2010)
This dissertation aims to discuss the phenomenon of metarepresentation in translation from a Relevance Theory-based analysis of expert translators inferential processes when dealing with unfamiliar contexts, i.e., a source text located in a considerabledistance of time, space, and culture in relation to the current audience. Starting from questions raised by Gutt (2000b) on how a translator acts when faced with a source text located in such an unfamiliar context, whether more analytically or intuitively, a decision was made to map the process of translation of a Talmudic text, sacred Jewishtext that fits within this category of unfamiliar contexts, in order to observe the metarepresentation processes taking place during the act of translation. Metarepresentation is addressed here from Gutts (2004) perspective, whereby the metarepresentation achieved through metareflection is the ability that humans have to represent how another person represents a state of affairs. The theoretical frameworkused for data analysis is Sperber & Wilsons (1986/1995) Relevance Theory with its application to translation by Gutt (1991/2000, among others) and Alves (2000a, 2000b, 2005, 2007, among others), and Carstons (2002) considerations with regard to explicatures and implicatures of the utterance. Key concepts such as conceptualencoding, procedural encoding, explicature, implicature, communicative clue and interpretive resemblance play a fundamental role in this dissertation, providing the theoretical framework for discussing the results. Methodologically, the technique of triangulation was used for data collection. Combining the techniques of direct observation, recording with Camtasia® software, and retrospective report, research wasconducted with 08 expert translators from Talmudic Hebrew to Portuguese. The source text selected for research is an excerpt from the Talmudic tractate Bava Metzia, Chapter 4, page 58b. Its translation presents the translators with challenges solved via metarepresentation. Explicitation was a recurring phenomenon in the target texts, discussed here according to Englund-Dimitrovas (2005) categorization of normgoverned explicitation and strategic explicitation, which highlights the tension between the fields of semantics and pragmatics. Accordingly, it was sought, likewise, to verify the hypothesis raised by Alves (2008) of an interrelationship between the categories proposed by Englund-Dimitrova, Steiner (2005), and Hansen-Schirra et al. (2007) andthe procedural and conceptual encodings. Finally, in analyzing the retrospective reports to identify instances of metareflection, capable of providing a more accurate metarepresentation enabling therefore the production of a target text with a high degree of interpretative similarity with the source text, it was sought to identify key elements for specific translation competence when translating texts located in an unfamiliarcontext.